Body Shaming in Terms of Gender Differences - Arnita, Fitri; Mayra, Zara; Fahmi, Kartika Wulan; Brescia, Reggiana; Fristy Yusri, Nada; Melamita, ⁠Anisa; Sari, Putri Fakhrina (INDONESIAN COUNSELING AND PSYCHOLOGY, 2025)
The phenomenon of body shaming has become a social problem that is increasingly prevalent in various circles, especially in the era of social media where physical appearance is the standard for self-assessment. Differences in perception and behavior between male and female often influence how people judge and convey other people's bodies. This study aims to describe differences in levels of body shaming behavior in terms of gender. This study is a comparative study with a sample of 160 people (male = 66; female = 94) obtained through a random sampling technique. Data analysis used an independent t-test to determine differences in body shaming behavior between male and female. The analysis results showed a t-value of 2.457 with a significance level of p < 0.015, which means there are significant differences in body shaming behavior based on gender. The results show that female have a higher tendency to be perpetrators of body shaming than male. This finding emphasizes the importance of implementing education and social interventions that consider gender aspects in efforts to reduce body shaming behavior in society.